Influences of Dispositional affect, Organisational Commitment and Organisation Climate on OCB among Health Professionals: Life Sciences-Psychology for curing mental health - Hassan Mahfooz Rao; Uzma Zaidi (International Journal of Life Science and Pharma Research, 2022)
In the rapidly changing world of health care, business, organisations and industries focus on maximising the potential benefits of workforce, products and services. The purpose of the study is to explore the concept of organisational citizenship behaviour and the factors that influence on OCB. Various studies found the connection between OCB and effective functioning of employees. Many factors affect personal behaviour, but this study focuses on exploring the relationship between affective disposition, organisation climate, organisational commitment and OCB among health professionals (N=400). This study also investigated the association of affective disposition, organisation climate, and organisational commitment as a predictor of organisational citizenship behaviour. The approach of this study was quantitative. The sample of this study consist of health professionals (N=384), having an age range of 30-50 years. A standardised questionnaire was used to measure dispositional affect, organisation climate, and organisational commitment and OCB. Participants were assured of confidentiality and instructed to choose their opinion without any hesitation. Results revealed the predictive association of affective disposition, organisation climate, organisational commitment with OCB (F (3,396) = 249.195, p<.01). In view of our result, we prescribe that it is vital to improving the workplace to empower specialists to advance their best and to decrease workplace disputes and crises. Employees who influence an organisation positively ought to be perceived and rewarded.